(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the theoretical and methodological foundations of teaching gijjak performance to students. It examines the step-by-step learning process, development of technical skills, cultivation of musical thinking, formation of artistic expression, and improvement of performance competence. The study outlines bowing techniques, left-hand finger independence, intonation accuracy, phrasing, rhythmic sensitivity, maqom traditions, and a system of practical exercises. The methodological recommendations contribute to improving educational programs and training professional performers specializing in gijjak.